ELITE PENENTU DALAM POLITIK LOKAL ( Studi Kasus Peran Ulama Terhadap Pemenangan Sofyan Caleg Dapil I Kecamatan Bantan Kabupaten Bengkalis Tahun 2014) - Bai Rahmat; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Political developments brought a number of theologian involved directly or indirectly in the political scene. theologian political aspirations exploited the political parties at national and local level in each general election. As a result, theologian faced with the world of politics, as happened on the legislative elections in Bengkalis District Bantan 2014, the scholars who contribute to winning one of the first candidate in the electoral district on behalf of the District Bantan Sofyan.The formulation of the problem in this research is how the role of the theologian against Sofyan winning candidate in the electoral district I Bengkalis District Bantan and what are the factors that influence the theologian involved to winning Sofyan. The purpose of this study to know how the role played by theologian in determining victory Sofyan, as well as for know what are the factors that influence the involvement of theologian against the winning Sofyan. This type of research is descriptive with qualitative approach. Informants in this study is, legislators Bengkalis, chairman of the foundation, chairman, director of KMI, Nurul Hidayah alumni of the boarding school, and the community Bantan. Data collection techniques with interviews to know how the role of the theologian against winning Sofyan. Qualitative data analysis technique that is performed on the data, in this case in the form of qualitative data is then associated with the data information other to gain clarity on the truth.The results of this study, the involvement of theologian against the winning Sofyan done by direct and indirect, As well as for factors that affect theologian support sofyan namely becaused by sofyan is alumni of pesantren Nurul Hidayah, so that if elected will sofyan education at boarding school always gets the full attention of the government.Keywords: Elite Determinants, Theologian, Local Politics